(untitled) (Journal of Physical Education (Maringá), 2016)
A pesquisa objetiva compreender a relação que os alunos estabelecem com os saberes aprendidos na Educação Física escolar e suas implicações para a constituição da especificidade desse componente curricular. Do tipo narrativa, define como colaboradores alunos do 6º e 9º anos do ensino fundamental de uma escola da Prefeitura Municipal de Vitória/Espírito Santo, sendo 30 discentes do 6º ano e 25 do 9º ano. Possui como instrumentos para produção das fontes: desenhos, explicações sobre os desenhos, grupos focais e entrevistas semiestruturadas. Pelo fato de a Educação Física ser uma disciplina que trabalha com as experiências e práticas corporais, os alunos tendem a associar o aprendizado dos conteúdos Ã ludicidade e ao prazer. Para compreender essa associação, analisam-se os processos de escolarização e a inserção da Educação Física nesse contexto. THE RELATION OF THE STUDENTS WITH KNOWLEDGES IN PHYSICAL EDUCATION CLASSES The research aims to understand the relation than students establish with the knowledges learned in school physical education and its implications for the constitution of the specificity of this curricular component. Of a narrative type, it defines students as collaborators of 6th and 9th grades of elementary education at a school of the City of Vitória/Espírito Santo, with 30 students in 6th grade and 25 in 9th grade. Features as tools for the production of sources: drawings, explanations of the drawings, focal groups and semi-structured interviews. Because physical education is a discipline that works with the experiences and bodily practices, the students tends to associate the learning content to the ludicity and pleasure. To understand this association, the processes of schooling are analyzed as well as the inclusion of physical education in this context.